Adoption of blended e-learning among Malaysian academicians - Haron, Haryani; Abbas, Wan Faezah; Abd Rahman, Nor Aini (2011)
The rapid growth of internet technologies creates a broader teaching and learning environment. Consequently, blended e-learning has been advocated and is considered as the most promising pedagogical approach that combines the use of electronic learning tools with traditional face-to-face classroom instruction component to maximize teaching effectiveness (Ng & Tsoi, 2008). Many universities are adopting blended e-Iearning since it offers human contact (Han & lung, 2008). Prasanna Ramakrisnan, Yuraidza Yahya, Mohd Nor Hajar Hasrol & Azlan Abdul Aziz (2009) stated that blended learning could help students to learn and help them to understand better in class. Many researchers believe that blended e-Iearning not only offers more choices but it is also more effective (Ng & Tsoi, 2008; Dziuban, Hartman & Moskal, 2004; Franklin & Harmelen, 2007; Lee & Chan, 2007). Observation by Agboola (2005), the implementation of e-Iearning tools has not kept pace with advances in technology. Most academic institutions seem not yet ready to deliver interactive online instruction, and as a result, the adoption of e-Iearning has been very slow, as well as blended e-Iearning. Studies have shown that academicians are apparently apprehensive about teaching In blended e-Iearning (Brooks, 2008). According to Russel (2008), academicians In traditional campus universities are apparently reluctant to adopt e-Iearning innovation in their teaching practice.